NORMA DAN ETIKA PEMANFAATAN FAKTOR-FAKTOR PRODUKSI DALAM SISTEM EKONOMI ISLAM - Rusdan, Rusdan (LP2M Institut Agama Islam Nurul Hakim, 2023)
The teachings of Islam place a strong emphasis on morality and ethics. In all activities, especially those involving production, every Muslim is expected to fulfill these moral standards. Production is typically understood as adding value to uses or creating new uses from existing ones. Economic activity will halt without output, and vice versa. Production activities incorporate a variety of elements, including but not limited to land, labor, capital, and organization, in order to generate commodities and services. In this study, a qualitative descriptive analytic research method was applied. While the methodology is a literature review, specifically research that uses library materials in the form of books, notes, and reports on the findings of other studies. Land, labor, capital, and organization are only a few of the variables that are utilised in manufacturing operations. The use of these production elements must take into account the applicable morals and ethical standards in the framework of Islamic economics. For this reason, land must be viewed as shared property with a social dimension that is focused on enhancing the socioeconomic welfare of the community; work is an obligation, in which the employer must be able to treat his workers fairly, pay wages on time, and provide workers with social facilities according to their abilities; capital is a mandate from Allah SWT. that must be managed properly and responsibly; and humans in the production organization occupy a crucial role.